The impact of brand equity on consumer buying behaviour among bottom of the pyramid consumers in South Africa: A case study of Parmalat yoghurt - Hlela, Sinegugu (School of Management Studies, 2020)
There has been significant research done on the impact of branding on consumer buying behaviour over the years, however, consumers at the bottom of the pyramid (BoP) have been ignored and very little research has been done in the South African market. This study examines the impact of brand equity on purchase intention of Parmalat yoghurt in the South African BoP market using socio-economic status, price sensitivity and sales promotion as mediating variables. Data was collected from 289 South African BoP consumers residing in Soweto. The study tested six hypotheses using PLS- SEM. Data was analysed using SmartPLS software. The results show that of the six hypotheses tested, only three are supported, namely, the relationship between brand equity and socio-economic status, socio-economic status and purchase intention and price sensitivity and purchase intention. Socio-economic status as a mediator has the most significant impact on the relationship between brand equity and purchase intention. The findings of this study give some implications for managers and marketers of yoghurt brands. Brand equity influences on purchase intention of yoghurt products and socio-economic status has the strongest mediating influence suggesting that companies must build and maintain strong brand equity in order to create a positive influence on purchase intention for their brands. Managers need to understand the underlying reasons as to why consumers would choose a competitor’s brand. Based on this study, socio-economic status and price sensitivity are the two most influencing mediators in the purchase intention of yoghurt, thus it is imperative for managers to take this into consideration when devising and implementing branding strategies.